Fictions of State : Culture and Credit in Britain, 1694-1994 - Brantlinger, Patrick (Book collections on Project MUSE., 2019)
In this ambitious book, Patrick Brantlinger offers a cultural history of Great Britain focused on the concept of ""public credit, "" from the 1694 founding of the Bank of England to the present.